Maternal hyperoxygenation improves left heart filling in fetuses with atrial septal aneurysm causing impediment to left ventricular inflow. (4th May 2015) - Channing, A.; Szwast, A.; Natarajan, S.; Degenhardt, K.; Tian, Z.; Rychik, J.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 630–630